The Contribution of Cognitive Ability and Affective Ability towards the Creative Thinking Skills of Senior High School Students by Using Innovative Learning in Industrial Agricultural Areas - Siswati, Bea Hana (Research Highlights in Language, Literature and Education Vol. 1, 2022)
Creative thinking skills are one of the important skills in learning. Several research results have reported the effect of various learning models on students’ creative thinking skills. This research aims at investigating the contribution of cognitive ability and affective ability on students’ creative thinking skills. This research uses descriptive quantitative research method with multiple linear regression analyses. The data were used to calculate the correlation coefficient and the significance of the correlation. Furthermore, the regression equation would be determined. The results of this research show that cognitive ability and affective ability have a positive correlation with students’ creative thinking skills. The effective contribution of the two variables towards students’ creative thinking skills is 88.6%.